2013
DOI: 10.1186/1475-2891-12-101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of legume kernel fibres and citrus fibre on putative risk factors for colorectal cancer: a randomised, double-blind, crossover human intervention trial

Abstract: BackgroundIn some studies, high intake of dietary fibre has been associated with a lower risk of colorectal cancer. The present study aimed to compare physiological effects of three legume kernel fibres and citrus fibre on blood lipids (primary outcome: LDL cholesterol) and colonic health.MethodsNinety-two subjects were recruited for the double-blind, controlled crossover trial. Seventy-eight participants were randomly divided into three groups. Following run-in, half the volunteers from each group consumed 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 42 publications
0
26
1
Order By: Relevance
“…Another Chinese study (Zhong et al, 2014) reported that soy fibre did not reduce the risk of colorectal cancer and suggested that some nutrients contained in soy food have protective effects against colorectal cancer. However, another study found that blue lupin kernel fibre could improve colonic function and had beneficial effects on decreasing the risk of colorectal cancer (Fechner et al, 2013). Grain fibre did not show an inverse association with colorectal cancer in our study, and a prospective study of 88757 women also did not report a significant relationship between grain fibre and the risk of colorectal cancer (Fuchs et al, 1999).…”
Section: Discussioncontrasting
confidence: 81%
“…Another Chinese study (Zhong et al, 2014) reported that soy fibre did not reduce the risk of colorectal cancer and suggested that some nutrients contained in soy food have protective effects against colorectal cancer. However, another study found that blue lupin kernel fibre could improve colonic function and had beneficial effects on decreasing the risk of colorectal cancer (Fechner et al, 2013). Grain fibre did not show an inverse association with colorectal cancer in our study, and a prospective study of 88757 women also did not report a significant relationship between grain fibre and the risk of colorectal cancer (Fuchs et al, 1999).…”
Section: Discussioncontrasting
confidence: 81%
“…The coarse fraction is a dry stream, has a protein content of 29 g/100, contains oil and is enriched in dietary fibre (see Appendix Table A1). The nutritive value of lupin fibres is high (Bähr et al, 2014;Kapravelou et al, 2013) and Fechner et al (2013) showed that the addition of 50 g dietary fibres (of L. angustifolius) to the human diet per day has beneficial physiological benefits; it improved colonic function and reduced risk factors for colorectal cancer. The SSF of the process contains protein, sugars and minerals.…”
Section: Valorisation Of Side Streamsmentioning
confidence: 98%
“…and certain butyrate producing bacteria (Prestamo et al, 2003;Huang et al, 2012;Ramnani et al, 2012;Cardona et al, 2013;Fechner et al, 2013;Duenas et al, 2015). At the same time, they suppress the growth of toxogenic E. coli and proteolytic bacteria like Clostridium perfringens, Streptococcus sp., peptococci, bacilli, Staphylococcus sp., bacteriodaeceae, pseudomonad, yeast and mould (Samarasinghe et al, 2003;Cao et al, 2005;Rohin et al, 2014;Asian J. Anim.…”
Section: Microbiological Attributesmentioning
confidence: 99%